Analysis of the Impact of the Middle Corridor on Turkiye in Terms of Geopolitics and Economy in the OBOR Initiative - Senol, Celal; Ucisik Erbilen, Suheyla (Istanbul Univ, Fac Letters, Dept Geography, 2022)
When the One Belt One Road (OBOR) Project was announced in 2013, it aimed to establish an uninterrupted transportation and commercial network between Asia and Europe. The Trans-European Networks (TEN) project initiated by the European Union (EU) and OBOR, which is considered an alternative to US-based commercial activities, has gained a global dimension in a short time. The OBOR project, which is planned as two lines of land and sea, concerns Turkey closely. These trade lines initiated by the EU and China will not only increase the geopolitical value of Turkey but also contribute to its economy. It is located on the Middle and South Corridors of the Turkish highway trade route. The Middle Corridor, which is predominantly built on a rail, reaches Europe through China, Central Asia, the Caucasus, and Turkey. The Southern Corridor will reach Europe by connecting to Turkey via Iran. The main purpose of these projects was to provide uninterrupted access between production and consumption centers. China wants to be the country that directs and controls world trade rather than exporting raw and processed products. For this reason, it has tended to establish close cooperation with countries at the intersection of continents, and Turkey is one of them. In this study, the relationship between the Middle Corridor between Turkey and China and its impact on the economy will be analyzed. Considering the impact of the country's geopolitical and geoeconomic structure and potential on the projects, a series of evaluations have been made.
Keywords: Turkey; Geopolitics and Geoeconomic; OBOR